2022
DOI: 10.3390/ijms23094693
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Mesenchymal Stem Cells Therapy and Osteoclasts in Osteoarthritis

Abstract: The use of mesenchymal stem cells constitutes a promising therapeutic approach, as it has shown beneficial effects in different pathologies. Numerous in vitro, pre-clinical, and, to a lesser extent, clinical trials have been published for osteoarthritis. Osteoarthritis is a type of arthritis that affects diarthritic joints in which the most common and studied effect is cartilage degradation. Nowadays, it is known that osteoarthritis is a disease with a very powerful inflammatory component that affects the subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 189 publications
1
11
0
2
Order By: Relevance
“…This study is lack of the verification of animal experiment that should be addressed in future experiments. Furthermore, osteoclasts are also a major contributor to OA development [58,59]. Thus, the effect of miR-338-3p-modified ASCderived exosomes on osteoclast activity needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This study is lack of the verification of animal experiment that should be addressed in future experiments. Furthermore, osteoclasts are also a major contributor to OA development [58,59]. Thus, the effect of miR-338-3p-modified ASCderived exosomes on osteoclast activity needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on the effectiveness of ASCs in treating osteoarthritis primarily address their ability to regenerate cartilage, there is emerging evidence of their ability to promote bone repair[ 61 ]. A study investigating the effect of ASCs on osteoclastogenesis, both in vitro and in a mouse model, demonstrated that RANKL-induced osteoclastogenesis was suppressed following ASC treatment[ 62 ].…”
Section: Ascs: Mechanism Of Actionmentioning
confidence: 99%
“…However, Chen et al have shown that autologous MSC(AT) injection significantly reduced the MOAKS for bone marrow lesions and cysts, meniscus pathology, and periarticular features at 48 weeks relative to baseline, while no significant differences were observed for osteophyte, synovitis, ligament tears or tendon abnormality scores [ 127 ]. In terms of subchondral bone, MSCs can interact with osteoclasts in OA through direct cell‒cell contact and indirectly through secreted factors and EVs to inhibit osteoclastogenesis and subchondral bone resorption, as recently reviewed [ 156 ]. Osteoblasts are also known to modulate cartilage metabolism and subchondral bone remodeling in OA, and a previous in vitro study demonstrated that EVs derived from human MSC(AT) reduced OA osteoblast senescence and the release of inflammatory mediators such as IL-6 [ 157 ].…”
Section: Msc Mechanisms Of Action In Knee Oamentioning
confidence: 99%